“Un re non è un cetriolo”. La figura del re Davide in Keter ba-rosh di Yaakov Shabtai (Altre Modernità, 2011)
The aim of this paper is to analyse King David’s character as it appears in the play Keter ba-rosh  written by Yaakov Shabtai in 1968-1969. In addition to the comparison with the original biblical  character, a deep survey of King David’s role in the play has been conducted in the order to explain  the different possible interpretations of the work. A particular attention is devoted to the affinity  between this play and the fictional work of the author.
Keywords: Yaakov Shabtai; re Davide